Distribution, genetic diversity and antimicrobial resistance of clinically important bacteria from the environment of a tertiary hospital in Malaysia - Phoon, H.Y.P.; Hussin, H.; Hussain, B.M.; Lim, S.Y.; Woon, J.J.; Er, Y.X.; Thong, Kwai Lin (Elsevier, 2018)
Objectives Hospital environments are potential reservoirs of bacteria associated with nosocomial infections. In this study, the distribution of cultivable environmental bacteria of clinical importance from a Malaysian tertiary hospital was determined and their resistotypes and genotypes were investigated.